2010
DOI: 10.4061/2010/540590
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Papillomatosis of Breast and Patient's Choice of Treatment

Abstract: Papillary lesions of breast represent a range of lesions. Intraductal papilloma and its association with nipple discharge are well known. However, multiple papillomatosis has quite distinct characteristics and decision making can be somewhat challenging. We report a case of multiple papillomatosis in association with ductal carcinoma in situ (DCIS). Patient opted for ipsilateral mastectomy and prophylactic mastectomy of contralateral breast. Her decision of having prophylactic mastectomy was vindicated by pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…A question that remains is how to determine solitary or multiple intraductal papillomas, whether by sonography, pathology, or both. Clinically, multiple papilloma is defined as the presence of at least five distinct independent papillomas in a segment of breast tissue, usually around or under the areola 2,41 . In ultrasound, solitary papilloma can be seen as an independent mass in the dilated mammary duct, a cystic or solid mass with a clear boundary 41,42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A question that remains is how to determine solitary or multiple intraductal papillomas, whether by sonography, pathology, or both. Clinically, multiple papilloma is defined as the presence of at least five distinct independent papillomas in a segment of breast tissue, usually around or under the areola 2,41 . In ultrasound, solitary papilloma can be seen as an independent mass in the dilated mammary duct, a cystic or solid mass with a clear boundary 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…2,41 In ultrasound, solitary papilloma can be seen as an independent mass in the dilated mammary duct, a cystic or solid mass with a clear boundary. 41,42 Yi W et al confirmed single papilloma by ultrasound, 43 and Zhu Y et al defined it with a histopathologic diagnosis of solitary intraductal papilloma. 44 Clinically, there are discordant conclusions between sonography and pathology.…”
Section: F I G U R E 4 Papillocarcinomamentioning
confidence: 99%
“…Clinically, multiple papilloma is defined as the presence of at least five distinct independent papillomas in a segment of breast tissue, usually around or under the areola. [2,41] . In ultrasound, solitary papilloma can be seen as an independent mass in the dilated mammary duct, a cystic or solid mass with a clear boundary.…”
Section: Discussionmentioning
confidence: 99%
“…In ultrasound, solitary papilloma can be seen as an independent mass in the dilated mammary duct, a cystic or solid mass with a clear boundary. [41,42] . Yi W et al confirmed single papilloma by ultrasound, [43] and Zhu Y et al defined it with a histopathologic diagnosis of solitary intraductal papilloma [44] .…”
Section: Discussionmentioning
confidence: 99%
“…İntraduktal papillomatozis, atipik duktal hiperplazi veya DKIS öncüsü olabilir. İntraduktal papillomatozisin DKIS'ya dönüşme oranı % 10-37,5 arasında değişmektedir (3) . Ciatto ve ark.…”
Section: Discussionunclassified